2019
DOI: 10.1021/acs.iecr.9b03865
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rhodamine-Derivated Dual-Responsive Colorimetric Fluorescent Chemoprobe for the Hypersensitive Detection of Ga3+ and Hg2+ and Biological Imaging

Abstract: A unique rhodamine-based derivative, 2-amino-3-(((1E,2E)-2-((3′,6′-bis­(diethylamino)-3-oxospiro­[isoindoline-1,9′-xanthen]-2-yl)­imino)­ethylidene)­amino)­maleonitrile (RhGDM), was easily fabricated just by Schiff-base condensation. RhGDM displays superb selectivity and sensitivity for specifically detecting the biologically and ecologically important Ga3+ and Hg2+ cations via a fluorescence “off–on” type in aqueous medium with high quantum yields and also the ultralow detection limits down to nanomolar level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…[1,[39][40][41] Similarly, 1 H NMR spectra of PCT and PCT-Al [42][43][44][45] The signals of H 10 split from a single peak into double peaks as a result of the imino N atom coordinated with Al 3 + , which limited the rotation of C=N and the chelation of PCT and Al 3 + forming two stable sixmembered ring structures. [46][47][48] The possible mechanism of sensing Ag + and Al 3 + is described in Scheme 1. The Schiff base N atom contributed to the photo-induced electron transfer (PET) phenomenon, which quenched the fluorescence of PCT.…”
Section: Recognition Mechanism Study Of Probe Pct With Ag + and Al 3 +mentioning
confidence: 99%
“…[1,[39][40][41] Similarly, 1 H NMR spectra of PCT and PCT-Al [42][43][44][45] The signals of H 10 split from a single peak into double peaks as a result of the imino N atom coordinated with Al 3 + , which limited the rotation of C=N and the chelation of PCT and Al 3 + forming two stable sixmembered ring structures. [46][47][48] The possible mechanism of sensing Ag + and Al 3 + is described in Scheme 1. The Schiff base N atom contributed to the photo-induced electron transfer (PET) phenomenon, which quenched the fluorescence of PCT.…”
Section: Recognition Mechanism Study Of Probe Pct With Ag + and Al 3 +mentioning
confidence: 99%
“…There are reports on the effects of various substitutions on rhodamine platforms on metal ion sensing properties. [31][32][33][34][35][36] Based on those background, in this work the linkage between the bisphenol A (Compound A) and rhodamine 6G (Compound B) derivative (Scheme 1) has been changed from hydrazine [30] to ethylene diamine unit to obtain RBA-IMS and the effect of this change on the sensing and separation properties has been investigated. And indeed, it was found to have a great effect on the sensing behavior of the resulting probe.…”
Section: Introductionmentioning
confidence: 99%
“…It showed Al 3+ , Cr 3+ , Fe 3+ and Cu 2+ sensing in ethanol while in water it could detect and separate Cu 2+ and Hg 2+ ions. There are reports on the effects of various substitutions on rhodamine platforms on metal ion sensing properties [31–36] . Based on those background, in this work the linkage between the bisphenol A ( Compound A ) and rhodamine 6G ( Compound B ) derivative (Scheme 1) has been changed from hydrazine [30] to ethylene diamine unit to obtain RBA‐IMS and the effect of this change on the sensing and separation properties has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…60 Whereas, thus far there are few DAMN-derived fluorescent chemoprobes for the specific detection of Hg 2+ , particularly by the hydrolysis mode, that have been reported. [61][62][63][64] Unfortunately, the previous works have shown that the single DAMN-based fluorescent chemoprobes can routinely detect Al 3+ instead of Hg 2+ . 65,66 Fortunately, Serkan Erdemir et al have reported a bistructure chemoprobe based on a fluorescein-phenolphthalein hybrid for the dual-channel fluorescent detection of Hg 2+ and Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%